1985
DOI: 10.1073/pnas.82.20.7086
|View full text |Cite
|
Sign up to set email alerts
|

Slow, persistent replication of lentiviruses: role of tissue macrophages and macrophage precursors in bone marrow.

Abstract: Lentiviruses, as exemplified by visna virus of sheep, are nononcogenic retroviruses that cause slowly progressive diseases after prolonged periods of incubation. Earlier studies on visna have shown that the long incubation period of the disease is associated with constant production of minimal quantities of virus in tissues, whereas virus could be obtained by culturing monocytes and macrophages from explants of lymphatic tissues and inflamed organs. In this study the role of macrophages in lentivirus infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
160
0
7

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(175 citation statements)
references
References 25 publications
8
160
0
7
Order By: Relevance
“…23 In addition to differences in the biology of T lymphocyte versus macrophage infection by HIV, differential viral infection and infectability of macrophage subpopulations is also evident. 24,25 Thus, the ability of HIV or SIV to infect macrophage subpopulations, and to become integrated within host DNA, may be regulated developmentally and controlled not only by surface receptors such as CD4, CXCR4, and CCR5, but by DNA metabolism.…”
Section: Brain Perivascular Macrophages Are a Major Target Of Simian mentioning
confidence: 99%
“…23 In addition to differences in the biology of T lymphocyte versus macrophage infection by HIV, differential viral infection and infectability of macrophage subpopulations is also evident. 24,25 Thus, the ability of HIV or SIV to infect macrophage subpopulations, and to become integrated within host DNA, may be regulated developmentally and controlled not only by surface receptors such as CD4, CXCR4, and CCR5, but by DNA metabolism.…”
Section: Brain Perivascular Macrophages Are a Major Target Of Simian mentioning
confidence: 99%
“…Visna virus principally targets macrophage in the brains and lungs of infected sheep (1). The more promiscuous feline immunodeficiency virus infects both T and B lymphocytes in addition to macrophage (2).…”
mentioning
confidence: 99%
“…= negative; sPCR = positive in first-round (single PCR) and in second-round PCR (nested PCR); nPCR = positive only in second-round PCR (nested PCR) *sample tested in a previous work (Preziuso et al 2009) and positive by sPCR The finding of both the proviral DNA and the viral capsid antigen in the mesenteric lymph nodes of sheep three years after infection by the respiratory route was unexpected. In only one case was a weak positivity in these lymph nodes reported in two lambs a few weeks after pulmonary inoculation (Gendelman et al 1985). Mesenteric lymph nodes have been suggested as a reservoir of HIV (Estaquier and Hurtrel 2008).…”
Section: Discussionmentioning
confidence: 99%
“…CAEV has been occasionally isolated from mammary lymph nodes, spleen and bone marrow (Surman et al 1997). The Ovine Lentivirus has also been isolated from the bone marrow (Brodie et al 1995), where viral replication has been demonstrated by combined immunocytochemistry and in situ hybridization in two lambs six or 16 weeks after virus inoculation (Gendelman et al 1985). Small ruminant lentivirus RNA or capsid proteins have occasionally been detected in macrophages or macrophage-like cells in the spleen (Zink et al 1990;Gendelman et al 1985;Zink et al 1990;Ravazzolo et al 2006).…”
Section: Discussionmentioning
confidence: 99%